Platelet Releasate Proteome Profiling Reveals a Core Set of Proteins with Low Variance between Healthy Adults. Issue 15 (15th July 2018) - Parsons, Martin E. M.; Szklanna, Paulina B.; Guerrero, Jose A.; Wynne, Kieran; Dervin, Feidhlim; O'Connell, Karen; Allen, Seamus; Egan, Karl; Bennett, Cavan; McGuigan, Christopher; Gheveart, Cedric; Ní Áinle, Fionnuala; et al.
Abstract: Upon activation, platelets release a powerful cocktail of soluble and vesicular signals, collectively termed the "platelet releasate" (PR). Although several studies have used qualitative/quantitative proteomic approaches to characterize PR; with debated content and significant inter‐individual variability reported, confident, and reliable insights have been hindered. Using label‐free quantitative (LFQ)‐proteomics analysis, a reproducible, quantifiable investigation of the 1U mL −1 thrombin‐induced PR from 32 healthy adults was conducted. MS proteomics data are available via ProteomeXchange, identifier PXD009310. Of the 894 proteins identified, 277 proteins were quantified across all donors and form a "core" PR. Bioinformatics and further LFQ‐proteomic analysis revealed that the majority (84%) of "core" PR proteins overlapped with the protein composition of human platelet‐derived exosomes. Vesicles in the exosomal‐size range were confirmed in healthy‐human PR and reduced numbers of similar‐sized vesicles were observed in the PR of a mouse model of gray platelet syndrome, known to be deficient in platelet alpha‐granules. Lastly, the variability of proteins in the PR was assessed, and reproducible secretion levels were found across all 32 healthy donors. Taken together, the PR contains valuable soluble and vesicular cargo and has low‐population variance among healthy adults, rendering it a potentially useful platform for diagnostic fingerprinting of platelet‐related disease.